Demokrat parti döneminde milliyetçilik - Yılmaz, Ercan (My University, 2008)
While DP came to power through ending the period of the single party covered 27 years, new and important time period has started in Turkish democratic and politic life, and government has changed hands firstly since the establisment of the Turkish Republic. DP, that developed a nationalist expression at the first years of the government, after some years began to recede this nationalist line unreadably, and moved away from the nationalist socety throuhgh following a policy like the period of CHP. After Nationalists Association has been closed by the the government on January 22, 1953, the first indifference began to seem between DP and nationalists. Hereafter a cold war continued between DP government and the nationalist society until the end of DP government, the relationships did not amend anyway. This closing event is a turning point similar to “Racism and Turanism Case” in 1944. In this time period Anatolianism and Turanism trends increased and Anatolianist Nationalism made its mark on this period as working actively. Although lots of nationalist magazine published in the period of DP government, some of these magazines were closed by the government because they were evaluated as chauvinst. At its government time, DP followed a nationalist foreign policy, conflicted with communism purposefully and executed a similar foreign policy to the concept of Ataturk’s time.
Keywords: Milliyetçilik; Partiler_Milliyetçilik; Siyaset ve Yönetim_Milliyetçilik; Tarih_Milliyetçilik